2020
DOI: 10.3389/fphar.2019.01499
|View full text |Cite
|
Sign up to set email alerts
|

Role of Estrogen Receptors α and β in a Murine Model of Asthma: Exacerbated Airway Hyperresponsiveness and Remodeling in ERβ Knockout Mice

Abstract: Epidemiological data suggests increased prevalence of asthma in females than males, suggesting a plausible role for sex-steroids, especially estrogen in the lungs. Estrogen primarily acts through estrogen-receptors (ERa and ERb), which play a differential role in asthma. Our previous studies demonstrated increased expression of ERb in asthmatic human airway smooth muscle (ASM) cells and its activation diminished ASM proliferation in vitro and airway hyperresponsiveness (AHR) in vivo in a mouse (wild-type, WT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 107 publications
(190 reference statements)
5
37
0
Order By: Relevance
“…Multiple groups, including our own, have shown a role for sex steroids, especially estrogen ( 3 5 , 12 , 15 17 , 21 , 22 , 31 , 33 , 37 39 ) and testosterone ( 11 , 18 , 22 , 24 , 27 ) in regulating the pathophysiology of lung diseases such as asthma or COPD as well as the known sex differences in these conditions ( 9 ). In this regard, sex steroids can differentially influence the expression and functionality of multiple signaling pathways in lung cells including ASM, contributing to altered airway reactivity and remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple groups, including our own, have shown a role for sex steroids, especially estrogen ( 3 5 , 12 , 15 17 , 21 , 22 , 31 , 33 , 37 39 ) and testosterone ( 11 , 18 , 22 , 24 , 27 ) in regulating the pathophysiology of lung diseases such as asthma or COPD as well as the known sex differences in these conditions ( 9 ). In this regard, sex steroids can differentially influence the expression and functionality of multiple signaling pathways in lung cells including ASM, contributing to altered airway reactivity and remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies, including our own, have reported a crucial role of sex-steroids on airway physiology, especially estrogen and its receptors (estrogen receptor, ERa, and ERb) in regulating the airway structure and function (18)(19)(20)(21)(22). From these studies, it is evident that estrogen differentially regulates airway physiology via diversified signaling of ERa versus ERb (detrimental vs. beneficial) in cellular aspects such as [Ca 2 þ ] i (21), proliferation (19), ECM (18) in vitro, and airway structure and function in vivo (22,23). However, the role of androgens in airway physiology remains unclear and is still being investigated.…”
Section: Introductionmentioning
confidence: 94%
“…Apart from their characteristic function in influencing reproductive organs, sex-steroids also influence a multitude of other organs and tissues eliciting their effects via sex-steroid receptors and regulate crucial cellular functions such as proliferation, migration, extracellular matrix (ECM) dynamics, intracellular calcium ([Ca 2 þ ] i ), and the local inflammatory milieu (9,11). Multiple studies, including our own, have reported a crucial role of sex-steroids on airway physiology, especially estrogen and its receptors (estrogen receptor, ERa, and ERb) in regulating the airway structure and function (18)(19)(20)(21)(22). From these studies, it is evident that estrogen differentially regulates airway physiology via diversified signaling of ERa versus ERb (detrimental vs. beneficial) in cellular aspects such as [Ca 2 þ ] i (21), proliferation (19), ECM (18) in vitro, and airway structure and function in vivo (22,23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect of tamoxifen is on breast tissue; however, its effect may not be limited to breast tissue alone. There is plenty of ER in the lung tissue [8]. It has been reported that tamoxifen may have an apoptotic effect on ER receptors in the lung tissue [9].…”
Section: Dear Sirmentioning
confidence: 99%